El Anatsui: Transformations - Binder, Lisa M. (African arts, 2008)
Chance was integral to his work with clay; when installing wood sculptures in galleries, there are almost always instructions for the sections to be arranged at the curators discretion; while working in residence, he tends to take a good deal of time reacting and responding to the space of the landscape before beginning; and most recently, the elements of his "cloth series" began when he found a pile of bottle-caps while looking around his studio for a "pot monument" (Fig. 1).1 Arguably, it is the cloth series that has garnered him the most attention from the Western art world in recent years. [...] in conversation with the artist, it became clear that this historical connection to a specific cloth type was secondary to the transformation of material and the significance of this change in relation to local and global political and societal conditions.2 As popular as the cloth sculptures are in Europe and America, the 2006 Dak'art Biennale marked the first time his work- Society Women's Cloth (2004)-was exhibited in Africa (Fig 2).